Dari Petani Markisa ke Petani Bawang: Kehidupan Sosial Ekonomi Petani di Nagari Air Dingin, Kecamatan Lembah Gumanti, Kabupaten Solok (2005-2022) - Suwarni, Siti; Midawati, Midawati (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2023)
This research discusses the socio-economic life of farmers in Nagari Air Dingin, Lembah Gumanti District, Solok Regency (2005-2022). This research uses historical research methods. The stages carried out are heuristics, source criticism, interpretation and historiography. Initially farmers in this area worked as passion fruit farmers. However, passion fruit only lasted for two decades and was replaced by onion crops. The causes are the eruption of Mount Talang, pest attacks on passion fruit stems, the difficulty of passion fruit growing again, land conversion and increasing development of onion cultivation. As a result, many farmers have switched from growing passion fruit to growing onions. The reason farmers choose to switch to onion plants is because onions have the opportunity to provide high yields and the increasing demand for onions. Apart from that, the transition from passion fruit to onions is also supported by geographical conditions that are suitable as an area for cultivating vegetable crops, especially onions.